The Socio-Political Approach in Viewing the Vaccination Programs in Indonesia - Desca Thea Purnama; Asrul Nur Iman; Alif Alfi Syahrin; Khosiruddin Khosiruddin; Nikodemus Niko (Kawanua International Journal of Multicultural Studies, 2021)
The current COVID-19 pandemic has led to more social segregation among the world’s people, including in Indonesia. This pandemic has created social, economic, and political inequality. The turning point for getting out of this pandemic is when the COVID-19 vaccine is discovered. This article discusses how politics plays a role in the vaccination program in Indonesia. The vaccination program has already started to be implemented in January 2021, following the issues of an emergency use approval (EUA) permit by Indonesia’s Food and Drug Supervisory Agency (Indonesia: Badan Pengawas Obat dan Makanan (BPOM)) and a halal (sacred) fatwa by the Indonesian Ulema Council (Indonesian: Majelis Ulama Indonesia (MUI)). At some stages of policy implementation, the government has not even been able to provide valid data related to the vaccination program. In this article, researchers explore the problems emerging concerning the COVID-19 vaccination program. Furthermore, researchers analyze the political agenda that is possible to become a health, social, and economic policy intervention in the corridor of the perspective of sociology.